Social Capital: A Panacea for HIV/AIDS Challenges in Uganda - Kabeba Muriisa, Roberts; Ishtiaq, Jamil (Journal of Development Issues, 2010)
Social capital is one of the most widely discussed and contested concepts in the social sciences. It has received wide attention from development practitioners, policy makers, and academia. Despite its growing importance for analyzing and explaining social economic and political outcomes, there are few or limited studies that have addressed the issues of the process through social capital is built and its eventual outcomes. As such, there is limited empirical research concerning social capital building and its practice in improving people’s health, especially in the context of developing countries. This paper discusses the role of NGOs in mobilising social capital and its effect on HIV/AIDS challenges. HIV/AIDS NGOs play a central role in the way individuals, groups and communities and state agencies interact and in this paper we argue that this is vital for people living with HIV/AIDS and especially for those who are HIV infected. We employed mixed research approaches to data collection and we collected both qualitative and quantitative data. The analysis also combined the analytical approaches. SPSS was used to generate quantitative data, while progressive and thematic data analysis approaches were used to analyse qualitative data. Inferring to this data and drawing lessons from other studies, the paper argues and concludes the mobilisation of social capital at the micro, meso and macro levels by HIV/AIDS organisations such as TASO and PTC/PLI has significantly contributed to the mitigation of HIV/AIDS challenges in Uganda.
Keywords: HIV/AIDS; Social Capital; NGOs; Synergy